Resin composition
Patent Information
- Application Number
- JP2021542720
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-05-27
- Filing Date
- 2020-08-12
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-08-12
AI Technical Summary
【0012】 本発明の樹脂組成物は、押出製造過程において成形外観不良をもたらすメヤニの発生が抑制され、且つ耐衝撃性に優れたものである。従って、本発明の樹脂組成物からなる成形体においては、外観及び耐衝撃性に優れ、OA機器、家電製品、食器、包装容器等の用途で有効に利用できる。
Smart Images

Figure 0007635129000001 
Figure 0007635129000002 
Figure 0007635129000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition which suppresses the generation of resin sludge in a die during extrusion production and has excellent impact resistance. [Background technology]
[0002] Taking advantage of their properties, styrene resins are used in a wide range of fields, including office equipment such as personal computers, printers, and copiers, and home appliances such as TVs and audio equipment.
[0003] On the other hand, polyester resins are excellent in mechanical properties and are therefore widely used in various industrial applications such as films, sheets, tableware, and packaging containers.
[0004] In recent years, there has been a demand for reducing carbon dioxide emissions due to the problem of global warming, and polylactic acid has attracted attention as one of the "carbon-neutral" polyester resins that apparently do not emit carbon dioxide. However, since polylactic acid is not very practical as a durable consumer product, polymer alloys with styrene-based resins and the like have been considered in recent years.
[0005] Polymer alloys of styrene resins and polylactic acid are usually produced by extrusion molding, and in this case, there are cases where scum due to resin decomposition products, undispersed additives, etc. occurs at the die outlet of the extruder. The scum that occurs is entrained in the strand and exists in a state adhering to the pellets after pelletization, which is problematic because it not only causes poor appearance of the pellets themselves, but also remains as colored dots on the surface of the molded product after molding processing such as injection molding, causing poor appearance. In addition, polylactic acid has a problem of low impact resistance, which was not sufficient even for polymer alloys of styrene resins and polylactic acid.
[0006] As a method for suppressing the appearance of the scum, a method of adding a higher fatty acid amide or a higher fatty acid alkali metal salt to a styrene-based resin composition containing polyphenylene ether is exemplified (Patent Document 1). However, this method does not have a sufficient effect of suppressing the appearance of the scum in a styrene-based resin composition containing a polyester-based resin such as polylactic acid.
[0007] In addition, as a method for improving impact resistance, a method of adding a copolymer of butadiene and an ethylenically unsaturated carboxylic acid ester to a styrene-based resin composition containing polylactic acid has been exemplified (Patent Document 2). However, although this method improves impact resistance, it has a problem of increasing the amount of scum generated at the die outlet during extrusion molding. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2012-41502 A [Patent Document 2] JP 2016-199654 A Summary of the Invention [Problem to be solved by the invention]
[0009] An object of the present invention is to provide a resin composition which is excellent in impact resistance and in which the generation of resin sludge in a die during extrusion production is suppressed. [Means for solving the problem]
[0010] The present inventors conducted extensive research to solve these problems and discovered that by blending an acrylic resin with a resin composition containing a styrene resin and a polyester resin and specifying the melt tension (MT), it is possible to reduce the amount of resin that forms on the die during the extrusion manufacturing process and obtain excellent impact resistance, thereby arriving at the present invention.
[0011] That is, the present invention is as follows. 1. A resin composition containing (A) a styrene-based resin and (B) a polyester-based resin, In a case where the total amount of the (A) styrene-based resin and the (B) polyester-based resin is 100 parts by mass, the (A) styrene-based resin is more than 50 parts by mass and 85 parts by mass or less, and the (B) polyester-based resin is 15 parts by mass or more and less than 50 parts by mass, (C) containing an acrylic resin; The (B) polyester-based resin is a polylactic acid having a lactide content of 0.01% by mass or more and 0.25% by mass or less, The (C) acrylic resin has a weight average molecular weight (Mw) of 1.5 million or more and 6 million or less and contains 60 mass% or more of methyl methacrylate as a structural unit, A resin composition having a melt tension (MT) measured at 200°C of 5 gf or more and 50 gf or less. 2. The resin composition according to the above item 1, wherein the (A) styrene-based resin is a rubber-modified polystyrene. 3 The above-mentioned 1, characterized in that the (C) acrylic resin is contained in an amount of 0.1 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the total amount of the (A) styrene-based resin and the (B) polyester-based resin. or 2 The resin composition according to claim 1. 4 The above-mentioned 1 to 3 characterized in that the total volatile matter content (TVM) contained in the (A) styrene-based resin is 500 ppm or less. 3 The resin composition according to any one of the preceding claims. Effect of the Invention
[0012] The resin composition of the present invention is excellent in impact resistance and suppresses the generation of scum that causes poor appearance during extrusion production. Therefore, the molded article made of the resin composition of the present invention is excellent in appearance and impact resistance, and can be effectively used for applications such as office automation equipment, home appliances, tableware, and packaging containers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The resin composition of the present invention will be described in detail below. The resin composition of the present invention has a melt tension value (MT) of 5 gf or more and 50 gf or less, measured at 200° C. The melt tension value is an index of the likelihood of seepage occurring when the resin composition is extruded, and a melt tension value of 5 gf or more exhibits an effect of suppressing the occurrence of seepage, while a melt tension value of 50 gf or less provides good extrusion moldability.
[0014] Next, the components of the resin composition of the present invention will be described. The resin composition of the present invention contains (A) a styrene-based resin, (B) a polyester-based resin, and (C) an acrylic-based resin.
[0015] First, the styrene resin (A) will be described. The styrene resin (A) used in the present invention is obtained by polymerizing a monomer of an aromatic vinyl compound. The aromatic vinyl compound monomer may be a known one such as styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, or 2,4-dimethylstyrene, but is preferably styrene. These monomers may be used alone or in combination. In addition, monomers such as acrylonitrile, (meth)acrylic acid, (meth)acrylic acid esters, and maleic anhydride that are copolymerizable with these monomers may be added and polymerized as long as they do not impair the performance of the styrene resin (A).
[0016] The total volatile matter content (TVM) contained in the (A) styrene-based resin is preferably 500 ppm or less. By keeping it 500 ppm or less, the amount of resin generated at the die outlet can be reduced, which is preferable. It is particularly preferable that it is 400 ppm or less.
[0017] The (A) styrene resin may be modified with a conjugated diene rubber polymer as required. Examples of the conjugated diene rubber polymer used for rubber modification include polybutadiene, random or block copolymers of styrene-butadiene, polyisoprene, polychloroprene, random, block or graft copolymers of styrene-isoprene, ethylene-propylene rubber, and ethylene-propylene-diene rubber, and polybutadiene, random, block or graft copolymers of styrene-butadiene are particularly preferred. These may also be partially hydrogenated.
[0018] Examples of such (A) styrene-based resins include polystyrene (GPPS), rubber-modified polystyrene (HIPS), ABS resin (acrylonitrile-butadiene-styrene copolymer), AS resin (acrylonitrile-styrene copolymer), MS resin (methyl methacrylate-styrene copolymer), AAS resin (acrylonitrile-acrylic rubber-styrene copolymer), AES resin (acrylonitrile-ethylene propylene-styrene copolymer), etc. Among these, rubber-modified polystyrene is particularly preferred because it can increase the impact resistance of the resin composition.
[0019] There is no particular restriction on the molecular weight of the matrix portion of HIPS, but the reduced viscosity (ηsp / C) of HIPS is preferably 0.5 to 1.0. Having a reduced viscosity of 0.5 or more is preferable because the molten strands of the resin are less likely to break, which is advantageous for stable production. Also, having a reduced viscosity of 1.0 or less is preferable because the fluidity of the molten resin can be secured.
[0020] The content of the rubber-like polymer in the HIPS is not particularly limited, but is preferably 3% by mass or more and 10% by mass or less. This range of the rubber-like polymer content is preferable because it provides a good balance between the impact resistance and rigidity of the molded product.
[0021] Next, the polyester resin (B) will be described. The polyester resin (B) used in the present invention is a general term for a polymer having an ester bond obtained by polymerizing a monomer containing a carboxylic acid and an alcohol.
[0022] (B) Polyester-based resins can be obtained, for example, by polymerization of dicarboxylic acids and diols. Examples of such polyester-based resins include polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polybutylene naphthalate, and further polyhexamethylene terephthalate and polyhexamethylene naphthalate, but the present invention is not limited to these.
[0023] Examples of the dicarboxylic acid component include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, and 4,4'-diphenylsulfonedicarboxylic acid. Other examples include aliphatic dicarboxylic acids such as adipic acid, suberic acid, sebacic acid, dimer acid, dodecanedioic acid, and cyclohexanedicarboxylic acid, and ester derivatives thereof. These carboxylic acid components may be used alone or in combination of two or more, and may further be partially copolymerized with oxyacids such as hydroxybenzoic acid.
[0024] Examples of the diol component include ethylene glycol, 1,2-propanediol, 1,3-propanediol, neopentyl glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, diethylene glycol, triethylene glycol, polyalkylene glycol, 2,2-bis(4-hydroxyethoxyphenyl)propane, isosorbate, and spiroglycol.
[0025] On the other hand, the (B) polyester resin can also be obtained by polymerizing a monomer having both a carboxylic acid and an alcohol in a single compound. An example of such a polyester resin is polylactic acid.
[0026] Among the above-listed polyester resins (B), polylactic acid is preferred from the viewpoint of carbon neutrality.
[0027] As the polylactic acid, poly(L-lactic acid) is used. From the viewpoint of reducing carbon dioxide emissions, plant-derived raw materials are preferred.
[0028] In the case of poly(L-lactic acid), the crystallization speed varies depending on the ratio of D-lactic acid contained as a monomer component. Considering the heat resistance and moldability of the resin composition of the present invention, poly(L-lactic acid) composed only of L-lactic acid is preferred, and when D-lactic acid is contained, its ratio is preferably 5.0 mol% or less. Particularly preferably, it is 1.5 mol% or less.
[0029] The molecular weight of polylactic acid is preferably in the range of 50,000 to 400,000 in weight average molecular weight (Mw), and more preferably in the range of 100,000 to 300,000.
[0030] The lactide content of the polylactic acid is preferably 0.01% by mass or more and 0.25% by mass or less in the polylactic acid, which is preferable because the amount of resin generated at the die outlet can be reduced by keeping the lactide content in this range.
[0031] The ratio of (A) styrene-based resin to (B) polyester-based resin is, when the sum of (A) styrene-based resin and (B) polyester-based resin is 100 parts by mass, (A) styrene-based resin is more than 50 parts by mass and not more than 85 parts by mass, and (B) polyester-based resin is 15 parts by mass or more and less than 50 parts by mass. By using (B) polyester-based resin in this ratio, it is possible to obtain an effect of reducing the environmental load, an effect of reducing the resin generated at the die outlet, and excellent impact resistance.
[0032] Next, the (C) acrylic resin will be described. In the present invention, the (C) acrylic resin refers to a polymer obtained by polymerization of an acrylic monomer, etc. The (C) acrylic resin has excellent compatibility with the (B) polyester resin, and therefore increases the melt tension value of the resin composition, thereby suppressing the occurrence of gum and improving impact resistance.
[0033] The weight average molecular weight (Mw) of the (C) acrylic resin is preferably 1.5 million or more and 6 million or less. The weight average molecular weight (Mw) of the acrylic resin is preferably in this range, since it suppresses gelation during extrusion molding while reducing the amount of scum and improving impact resistance. The amount of the (C) acrylic resin added is preferably 0.1 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the total of the (A) styrene resin and the (B) polyester resin. The weight average molecular weight (Mw) of the (C) acrylic resin is preferably in this range, since it suppresses gelation during extrusion molding while reducing the amount of scum and improving impact resistance.
[0034] The type of acrylic monomer constituting the (C) acrylic resin is not particularly limited as long as it does not impair the effects of the present invention. For example, a homopolymer of an acrylate monomer such as methyl acrylate, ethyl acrylate, isopropyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, benzyl acrylate, cyclohexyl acrylate, phenyl acrylate, or chloroethyl acrylate, or a homopolymer of a methacrylate monomer such as methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, benzyl methacrylate, cyclohexyl methacrylate, phenyl methacrylate, or chloroethyl methacrylate, or a copolymer obtained by copolymerizing two or more of these monomers can be used.
[0035] The (C) acrylic resin preferably contains 60% by mass or more of methyl methacrylate as a structural unit. When the (C) acrylic resin contains methyl methacrylate units in this range, the melt tension value of the resin composition is increased, the resin composition exhibits a resin-stain suppressing effect, and the impact resistance is improved. The content of 75% by mass or more is particularly preferred.
[0036] The (C) acrylic resin may be one obtained by adding and polymerizing, in addition to these acrylic monomers, vinyl monomers copolymerizable therewith, so long as the effects of the present invention are not impaired. For example, monomers such as α-olefins, vinyl aromatics, unsaturated nitriles, unsaturated carboxylic acids or esters thereof, and polyunsaturated compounds such as ethylene glycol di(meth)acrylate may be added.
[0037] Examples of the polymerization method for the (C) acrylic resin include known polymerization methods such as emulsion polymerization, soap-free emulsion polymerization, fine suspension polymerization, suspension polymerization, bulk polymerization, solution polymerization, etc. Among these polymerization methods, emulsion polymerization is preferred because it is easy to produce a high molecular weight substance.
[0038] As the emulsifier used when producing the (C) acrylic resin by emulsion polymerization, a known emulsifier can be used, such as an anionic emulsifier, a nonionic emulsifier, a polymer emulsifier, or a reactive emulsifier having a radically polymerizable unsaturated double bond in the molecule.
[0039] To the resin composition of the present invention, other additives such as plasticizers, spreading agents, solvents, ultraviolet absorbers, antioxidants, antiaging agents, light stabilizers, stabilizers, antistatic agents, colorants, dyes and pigments, fillers, color inhibitors, reinforcing agents, compatibilizers, crystallization accelerators, flame retardants, flame retardant assistants, etc. can be added and polymerized within the scope of the present invention.
[0040] In particular, MBS as a reinforcing agent, talc as a crystallization promoter, and liquid paraffin as a spreading agent can be suitably added. MBS is a copolymer of methyl methacrylate, butadiene, and styrene, and has good dispersibility with any of (A) styrene-based resin, (B) polyester-based resin, and (C) acrylic resin, and is preferable because it can efficiently reinforce the impact resistance of the resin composition of the present invention. Talc is preferable because it can promote the crystallization of (B) polyester-based resin in the present invention and can improve the mechanical strength of the resin composition. Liquid paraffin is a saturated hydrocarbon refined by removing impurities such as aromatic hydrocarbons and sulfur compounds contained in the lubricating oil fraction of petroleum with sulfuric anhydride or fuming sulfuric acid, and can suppress classification between resins with different specific gravities when mixing the resin composition of the present invention, and is therefore preferable because it can suppress quality variation of the resin composition during extrusion production.
[0041] The method of adding the additives is not particularly limited, and may be a known method. For example, the additives may be added in a raw material charging step, polymerization step, or finishing step during the production of the (A) styrene-based resin or (B) polyester-based resin, or in a step of mixing the resin composition using an extruder or molding machine.
[0042] Next, a method for producing the resin composition of the present invention will be described. The method for producing the resin composition of the present invention is not particularly limited, and known mixing techniques can be applied. For example, various raw materials are mixed in advance using a mixing device such as a mixer-type mixer, a V-type blender, and a tumbler-type mixer, and the mixture is melt-kneaded to produce a homogeneous resin composition. The melt-kneading device is also not particularly limited, and examples thereof include a Banbury type mixer, a kneader, a roll, a single-screw extruder, a special single-screw extruder, and a twin-screw extruder. Furthermore, there is also a method in which other additives are added separately from the middle of a melt-kneading device such as an extruder.
[0043] The molding method for obtaining a molded article from the resin composition of the present invention is not particularly limited, and known molding methods such as extrusion molding methods such as calendar molding, blow molding, extrusion foam molding, profile extrusion molding, lamination molding, inflation molding, T-die film molding, sheet molding, vacuum molding, and pressure molding, and injection molding methods such as injection molding, RIM molding, and injection foam molding can be suitably used, with injection molding or sheet molding being preferred. EXAMPLES
[0044] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to these.
[0045] The materials and measurement methods used in the examples and comparative examples are as follows. 〔material〕 (styrene resin) A-1: HIPS (manufactured by Toyo Styrene Co., Ltd.) Reduced viscosity: 0.89 dl / g Rubber polymer content: 6.9% by mass Charpy impact strength: 11kJ / m 2 Melt tension value (MT): 4gf Total volatile matter (TVM): 200 ppm A-2: GPPS (manufactured by Toyo Styrene Co., Ltd.) Reduced viscosity: 0.94 dl / g Charpy impact strength: 2.1kJ / m 2 Melt tension value (MT): 4gf Total volatile matter (TVM): 250 ppm A-3: MS resin (manufactured by Toyo Styrene Co., Ltd.) Reduced viscosity: 0.50 dl / g Charpy impact strength: 1.0kJ / m 2 Melt tension value (MT): 20gf Total volatile matter (TVM): 450 ppm Methacrylic acid monomer unit content: 8% by mass A-4: HIPS (manufactured by Toyo Styrene Co., Ltd.) Reduced viscosity: 0.80 dl / g Rubber polymer content: 5.1% by mass Charpy impact strength: 10kJ / m 2 Melt tension value (MT): 2gf Total volatile matter (TVM): 600 ppm
[0046] (Polyester resin) B-1: Polylactic acid (“REVODE190” manufactured by Zhejiang Hisun Biomaterials Co., Ltd.) Ratio of D-lactic acid component: 0.5 mol% Weight average molecular weight (Mw): 200,000 Lactide content: 0.20% by mass B-2: Polylactic acid (NatureWorks "Ingeo4032D") Ratio of D-lactic acid component: 1.5 mol% Weight average molecular weight (Mw): 190,000 Lactide content: 0.30% by mass B-3: Polylactic acid (NatureWorks "Ingeo2500HP") Ratio of D-lactic acid component: 0.5 mol% Weight average molecular weight (Mw): 190,000 Lactide content: 0.13% by mass B-4: PET (Eastman "PET-G GN001")
[0047] (Acrylic resin) The acrylic resin (C-1) was produced by the following method. Into a separable flask (capacity 5 liters) equipped with a thermometer, a nitrogen inlet tube, a cooling tube and a stirrer, 300 parts by mass (3000 g) of ion-exchanged water as a dispersion medium, 1.1 parts by mass of sodium dodecylbenzenesulfonate as an emulsifier, 0.007 parts by mass of n-octyl mercaptan as a chain transfer agent, 85 parts by mass of methyl methacrylate as a monomer, and 15 parts by mass of butyl acrylate were added. The atmosphere in the flask was replaced with nitrogen by passing a nitrogen stream through the separable flask. Next, the internal temperature was raised to 60°C, and 0.15 parts by mass of potassium persulfate and 5 parts by mass of deionized water were added. After that, the mixture was heated and stirred for 2 hours to terminate the polymerization, and an acrylic resin latex was obtained.
[0048] The obtained acrylic resin latex was cooled to 25°C, then dropped into 500 parts by mass of 70°C warm water containing 5 parts by mass of calcium acetate, and then heated to 90°C to cause coagulation. The obtained coagulated product was separated and washed, and then dried at 60°C for 12 hours to obtain acrylic resin (C-1).
[0049] The amounts of various raw materials charged were adjusted and acrylic resins (C-2) to (C-6) were obtained under the same production conditions as above. The weight average molecular weight (Mw) and the content of methyl methacrylate units of the obtained acrylic resins are shown in the table.
[0050] [Table 1]
[0051] (Additives) D-1: Polycarbodiimide ("LA-1" manufactured by Nisshinbo) D-2: Oxazoline group-containing polymer (Nippon Shokubai "RPS1005") D-3: Epoxidized soybean oil (NOF "N-510")
[0052] [Method for measuring reduced viscosity (ηsp / C)] A mixed solvent of 17.5 ml of methyl ethyl ketone and 17.5 ml of acetone was added to 1 g of styrene resin, and the mixture was dissolved by shaking at 25°C for 2 hours. The insoluble matter was then precipitated by centrifugation, the supernatant was removed by decantation, 250 ml of methanol was added to precipitate the resin matter, and the insoluble matter was filtered and dried. The resin matter obtained by the same procedure was dissolved in toluene to prepare a sample solution with a polymer concentration of 0.4% (mass / volume). The solution flow time in seconds for this sample solution and pure toluene was measured at a constant temperature of 30°C using an Ubbelohde viscometer, and the calculation was performed using the following formula. ηsp / C=(t1 / t0-1) / C t0: Pure toluene flow time in seconds t1: sample solution flow time in seconds C: Polymer concentration
[0053] [Method of measuring rubber polymer content] HIPS was dissolved in chloroform, a certain amount of iodine monochloride / glacial acetic acid solution was added, and the mixture was left in a dark place for approximately 30 minutes. After that, a 15% by mass potassium iodide solution and 50 ml of pure water were added, and the excess iodine monochloride was titrated with 0.1 N sodium thiosulfate solution, and the amount of iodine monochloride added was calculated.
[0054] [Method of measuring Charpy impact strength] The Charpy impact strength of the styrene-based resin and the resin composition was measured according to JIS K7111 and the ISO179 / 1eA method.
[0055] [Melt tension (MT) measurement method] Using "Capillograph 1B" manufactured by Toyo Seiki Co., Ltd., a styrene resin or resin composition was extruded at a barrel temperature of 200°C, a barrel diameter of 9.55 mm, a capillary length: L = 10 mm, a capillary diameter: D = 1 mm (L / D = 10), and an extrusion speed in the barrel of 10 mm / min. The load measurement part was set 60 cm below the die, and the strand-shaped resin flowing out from the capillary was set on a winder, and the winding linear speed was increased from 4 m / min to 200 m / min at a rate of 20 m / min per minute, and the load until the strand broke was measured. As the winding linear speed was increased, the load increased and stabilized at a certain fluctuation range, but since there was a fluctuation range in the load, the range from when the load stabilized to when it broke was averaged and used as the melt tension value (MT).
[0056] [Method of measuring total volatile matter (TVM)] 500 mg of styrene resin was dissolved in 10 ml of dimethylformamide (DMF) containing cyclopentanol as an internal standard substance, and the contents of volatile components (styrene monomer, toluene, ethylbenzene, cyclohexane, xylene) were measured using a gas chromatograph. Gas chromatograph: Hewlett-Packard "HP-5890" Column: "HP-WAX", 0.25 mm x 30 m, film thickness 0.5 μm Injection temperature: 220℃ Column temperature: 60℃~150℃, 10℃ / min Detector temperature: 220℃ Split ratio: 30 / 1
[0057] [Method of measuring weight average molecular weight (Mw)] The weight average molecular weight (Mw) of the polyester resin and the acrylic resin was measured by gel permeation chromatography (GPC) under the following conditions. GPC model: Showa Denko Co., Ltd. "Shodex GPC-101" Column: Polymer Laboratories "PLgel 10μm MIXED-C" Mobile phase: Chloroform Sample concentration: 0.2% by mass Temperature: Oven 40℃ Detector: Differential refractometer In the present invention, the molecular weight of each component is measured by calculating the molecular weight at each elution time from the elution curve of monodisperse polystyrene, and calculating the molecular weight in terms of polystyrene.
[0058] [Method for measuring the ratio of D-lactic acid components] 0.3 g of polylactic acid was weighed out, added to 6 mL of 1N potassium hydroxide / methanol solution, and thoroughly stirred at 65°C. Then, 450 μL of sulfuric acid was added, and stirred at 65°C to decompose the polylactic acid, and 5 mL was measured as a sample. This sample was mixed with 3 mL of pure water and 13 mL of methylene chloride and shaken. After standing and separating, about 1.5 mL of the lower organic layer was collected, filtered with a 0.45 μm pore size HPLC disk filter, and then measured by gas chromatography using a Hewlett-Packard "HP-6890 Series GC System". The ratio (%) of the peak area of D-lactic acid methyl ester to the total peak area of lactate methyl ester was calculated, and this was taken as the ratio (content, mol%) of the D-lactic acid component in polylactic acid.
[0059] [Method for measuring lactide content] 250 mg of polylactic acid was dissolved in 25 ml of diphenyl ether (DPE), and 3 ml of dichloromethane was added to completely dissolve the sample. Then, N-hexane was added to the solution to make a constant volume, and about 1.5 mL of the supernatant was taken. After filtering with a 0.45 μm pore size HPLC disk filter, the lactide content of polylactic acid was measured using a gas chromatograph. Gas chromatograph: Shimadzu Corporation "GC-2014" Column: "SUPELCO SPB-5"
[0060] [Method for measuring methyl methacrylate unit content] The content of methyl methacrylate units in the acrylic resin was measured as shown below based on the analytical method of Example 7 of JP-A No. 2001-141725.
[0061] 0.1023g of acrylic resin and 3.4613g of ethanol were charged into an autoclave (SUS316, internal volume 9ml, with pressure gauge) and the reaction was started by heating to 300°C in a sand bath. After 60 minutes, the autoclave was rapidly cooled, and after returning to room temperature, the reaction liquid was removed from the autoclave. The reaction liquid was filtered and the volume was adjusted to 10ml with ethanol. The alcohol obtained as the product was detected using a Hewlett-Packard gas chromatograph "HP5890" equipped with a J&W Scientific "DB-WAX" type column and an FID detector. The detected alcohol was quantified using the calibration curve method, and the content of methyl methacrylate monomer was calculated.
[0062] (Examples 1 to 11, Comparative Examples 1 to 10) The above-mentioned styrene-based resin, polyester-based resin, acrylic-based resin, and additives were premixed in the amounts (parts by mass) shown in Tables 2 and 3 in a Henschel mixer ("FM20B" manufactured by Mitsui Miike Chemical Co., Ltd.), fed into a twin-screw extruder ("TEM26SS" manufactured by Toshiba Machine Co., Ltd.) to form strands, cooled with water, and then fed into a pelletizer to be pelletized.
[0063] After 50 kg of strands were extruded by the twin-screw extruder, the amount of resin was visually observed at the die outlet and judged according to the following criteria. 1: Eye scum was observed within 10 kg after extrusion. 2: Eye scum was observed within 20 kg after extrusion. 3: Eye scum was observed within 30 kg after extrusion. 4: Eye scum was observed within 40 kg after extrusion. 5: No eye mucus was observed.
[0064] [Table 2]
[0065] [Table 3]
[0066] From the examples in Table 2, it can be seen that the resin composition of the present invention has a small amount of scum and is excellent in impact resistance. On the other hand, from Comparative Examples 3 to 5 in Table 3, it can be seen that additives of known techniques that improve the melt tension value (MT) of polylactic acid are not sufficiently effective for the resin composition of the present invention. In addition, from the Comparative Examples, it can be seen that resin compositions that do not satisfy the specifications of the present invention have a large amount of scum or are inferior in impact resistance.
Claims
1. A resin composition containing (A) a styrene-based resin and (B) a polyester-based resin, In a case where the total amount of the (A) styrene-based resin and the (B) polyester-based resin is 100 parts by mass, the (A) styrene-based resin is more than 50 parts by mass and 85 parts by mass or less, and the (B) polyester-based resin is 15 parts by mass or more and less than 50 parts by mass, (C) containing an acrylic resin, The (B) polyester-based resin is a polylactic acid having a lactide content of 0.01% by mass or more and 0.25% by mass or less, The (C) acrylic resin has a weight average molecular weight (Mw) of 1.5 million or more and 6 million or less, and contains 60 mass% or more of methyl methacrylate as a structural unit, A resin composition having a melt tension (MT) measured at 200°C of 5 gf or more and 50 gf or less.
2. 2. The resin composition according to claim 1, wherein the styrene-based resin (A) is a rubber-modified polystyrene.
3. The resin composition according to claim 1 or 2, characterized in that it contains 0.1 parts by mass or more and 10 parts by mass or less of the acrylic resin (C) relative to 100 parts by mass of the total amount of the styrene-based resin (A) and the polyester-based resin (B).
4. 4. The resin composition according to claim 1, wherein the styrene-based resin (A) has a total volatile matter content (TVM) of 500 ppm or less.
Citation Information
Patent Citations
Manufacture of styrenic resin
JP1996318529A
Rubber modified styrene-based resin and its composition
JP1998087759A
Thermoplastic elastomer resin composition
JP1999323031A
Thermoplastic resin composition and molded article using the same
JP2003147213A
Thermoplastic resin composition
JP2006045487A